Facile Fabrication of Nanoporous Bi2WO6 Photoanodes for Efficient Solar Water Splitting. Issue 11 (1st June 2017) - Dong, Guojun; Zhang, Yajun; Wang, Wei; Wang, Lei; Bi, Yingpu
Abstract: Nanoporous bismuth tungsten oxide (Bi2 WO6 ) photoanodes are synthesized by using a facile drop‐casting strategy for one‐step fabrication. The Bi2 WO6 photoanode exhibits significantly improved solar photo‐electrochemical capability for water oxidation. The photocurrent density is nearly 10 times higher than the traditional particle photoanodes. In addition, synchronous illumination X‐ray photoelectron spectroscopy (SIXPS) was employed to directly identify the charge separation and electron transfer in the nanoporous Bi2 WO6 photoanodes, which clearly reveals that the electrons transfer from the Bi and W atomic sites to the O sites. These demonstrations provide further new insights into the origin of high efficiency in nanoporous photoanodes, which may be promising for the rational construction of solar conversion and storage devices. Abstract : Performing the splits : Nanoporous Bi2 WO6 photoanodes are synthesized by a facile drop‐casting strategy for one‐step fabrication. The Bi2 WO6 photoanode exhibits significantly improved solar photo‐electrochemical capability for water oxidation. The photocurrent density is nearly 10 times higher than the traditional particle photoanodes. Synchronous illumination X‐ray photoelectron spectroscopy (SIXPS) is employed to directly identify the charge separation and electron transfer in the nanoporous Bi2 WO6 photoanode.